Salmonella infection induced intestinal crypt hyperplasia through Wnt/β-catenin pathway in chicken. (June 2020) - Xie, Shuang; Li, Yuchen; Zhao, Shiyi; Lv, Yingjun; Yu, Qinghua
Abstract: S. Pullorum is a causative agent of enteric disease of poultry with serious diarrhea. However, the detailed mechanism behind its injury to intestinal mucosa barrier, especially for intestinal stem cells, is unclear. In this study, S. Pullorum were orally administrated to 3 days old chicken to investigate the pathogenesis of S. Pullorum on intestinal mucosal barrier, especially on the proliferation of epithelial cells. We found that S. Pullorum could colonize in the cecum and invade into the liver through intestinal mucosa damage, which caused obvious pathological changes in liver and intestine and even leaded to death, as well as significant reduction of body weight. We also found that S. Pullorum infection enhanced the mRNA expression of IL-1β and IL-6 through TLR4/MyD88 pathway, which was also further verified by the increased lipopolysaccharide (LPS) levels in serum. Furthermore, S. Pullorum increased the depth of crypt and density of PCNA + cells significantly through the over-activation of Wnt/β-catenin signaling pathway. The expression of intestinal stem cells markers Lgr5 and Bmi1 was also increased after S. Pullorum infection to support the crypt hyperplasia. In addition, we verified that S. Pullorum infection enhanced the mRNA expression of IL-1β, TLR4, Lgr5 and Bmi1. Our study indicated that S. Pullorum infection damaged the intestinal mucosa barrier to induce diarrhea, affected the abnormal proliferation of intestinal stem cells by over-activation of Wnt/β-catenin pathway in chicken. Highlights: S. Pullorum infection causes hepatic and intestinal pathological changes. S. Pullorum damages intestinal barrier through TLR4/Myd88 pathway. S. Pullorum over-activates Wnt/β-catenin pathway with crypt hyperplasia.